Income and Outcomes: A Structural Model of Intrahousehold Allocation - Browning, Martin; Bourguignon, François; Chiappori, Pierre-André; Lechene, Valérie (Journal of Political Economy, 1994)
There is evidence from several sources that one cannot treat many-person households as a single decision maker. If this is the case, then factors such as the relative incomes of the household members may affect the final allocation decisions made by the household. We develop a method of identifying how "incomes affect outcomes" given conventional family expenditure data. The basic assumption we make is that household decision processes lead to efficient outcomes. We apply our method to a sample of Canadian couples with no children. We find that the final allocations of expenditures on each partner depend significantly on their relative incomes and ages and on the level of lifetime wealth.